The Effect of the Combination Stimulation Cutaneous and Virgin Coconut Oil on the Sleep Quality and Comfort level in People Undergoing Hemodialysis - Putu Intan Daryaswanti; Elyana Asnar; Ilya Krisnana (Babali Health, 2022)
Introduction: Sleep quality can be disruptive in patients with chronic illness, especially in patients with Chronic Renal Failure (CRF). In recent times, CRF was associated with poor sleep quality, about 25-36% of the normal adult population had sleep disorders. However, the prevalence of sleep disturbance in patients with uremia undergoing of hemodialysis occurs about 40-85% higher than the general population. It was reported that the majority of cases of chronic renal failure are people who lack sleep. Sleep disorders are very common in patients with chronic kidney disease. Poor sleep in hemodialysis patients has a negative impact on the physical and mental components of a person's life and leads to a decrease in their performance as well as cognitive and memory dysfunction. Methods: A queasy-experiment with pretest-posttest control group design. The sampling method is used simple random sampling, conducted between January-February 2018. A total of 52 patients undergoing hemodialysis divided randomly into two groups. The treatment group was given cutaneous stimulation and VCO for 4 weeks and the control group was not given cutaneous stimulation and VCO. Results: Giving cutaneous stimulation and VCO effective in improving sleep quality and comfort level. There were significant results on sleep quality seen from Mann Whitney test with p <.001 and comfort level from Mann Whitney test with p = 0.009. Conclusion: Provision of cutaneous stimulation and VCO can be used as complementary therapy in improving quality of sleep and comfort in patients undergoing hemodialysis.